Extended T-Type Boost Inverter for Capacitance Reduction - Sugimoto, Tomoya; Nozaki, Takahiro; Murakami, Toshiyuki (IEEE International Conference on Industrial Technology (Online), 2020)
In these days, multilevel inverters are focused thanks to their advantages, such as small voltage stress, low electromagnetic interferences, and harmonics reduction. Generally, renewable energy sources output a low DC voltage. From the viewpoint of efficiency, a single-stage conversion system which can directly change the lower DC-link voltage to higher AC voltage is required. Some single-stage conversion systems have been proposed before. However, these systems have large energy storage such as an inductor and a capacitor. This paper proposes a multilevel boost inverter stepping up the AC output peak voltage at any boost ratio by changing the number of switched capacitors. To reduce the capacitance, the proposed inverter has multiple conduction patterns when the output voltage is boosted. This characteristic distributes the discharging time to multiple capacitors. This inverter can set any maximum boost ratio and apply to the multiphase applications. The operation principle and the boost ability with multiple boost ratios were confirmed by simulations and experiments. The capacitance reduction was also confirmed by simulations.